Rotasi Kerja Sebagai Strategi Peningkatan Kinerja Perawat - Giri Susilo Adi (Jurnal Keperawatan Notokusumo, 2018)
The quality of good nursing services is one of the important factors in creating patient satisfaction. Many factors influence nursing services, one of which is the work rotation system in the management of human resource management. The purpose of this study is to determine the effectiveness of work rotation as a strategy to improve nurse performance. Work rotation is the transfer of employees to increase the effectiveness and productivity of employees in the organization and this will help employees learn new skills, reduce boredom and eliminate job dissatisfaction. The results of various literature studies show that well-managed work rotation will have an effective impact on improving nurse performance.